The impact of digital Leadership in the adoption of the organization culture of the staff of the directorate of education in the governorate of Najaf in Iraq - Al Tai, Yousef Hajim Sultan; Al-Hadrawi, Baqir Khudair Abdul Abbas (Journal of Economic, Administrative and Legal Sciences, 2019)
The purpose of study is to explore The impact of digital Leadership in The adoption of the organization culture and rescan hers have used description approach , it as a tool in resolution in gathering information and data for that study ,Resolution were distributed on 85 officer in Najaf Department of Education , And the analysis done with use the Statistical program (SPSS(, The outcome indicated the access to the digital leadership on general average amount (3.17) ,and at the level of dimensions ,and it got the averages (3.35، 3.44، 2.71), for all of them respectively, and the axis of organizational culture got the total average (3.95), and there is positive correlation relationship the total average value amount (0.624), so that the application of digital Leadership is expedite in staff development through the light result of the study , we have been make set of recommendations in clouding that priorities attention impact elements digital Leadership in organization culture to obtain on impact and effectiveness of the digital Leadership in organization culture so we should be arranged of the digital Leadership priorities to achieve organization goals.